Heart Failure Patients’ Perceptions of Quality of Life: A Meta-Synthesis - Wilkinson, Amy Elisabeth (2013)
Background: The prevalence of heart failure is increasing due to increased life expectancy and increased survival following cardiac events. Heart failure affects quality of life more than most other chronic conditions, and in many cases, maintaining quality of life is more important than increasing survival. Objectives: To date there is no literature review combining quality of life and heart failure. A meta-synthesis was conducted to gain an insight into patient perceptions of quality of life with heart failure, in order to fill this gap in research. Search strategy: Cinahl, Medline, Embase and PsychInfo were searched using key search terms identified through combining PICO and SPIDER. Reference lists of relevant articles were examined for any research papers that may have been missed, until no new articles were found. Inclusion criteria: Primary qualitative research conducted in English was included. It was imperative that participants had a diagnosis of heart failure and that the research focus was on the patients‟ perspectives. Data analysis: Interpretative phenomenological analysis was used to extract and synthesise the data from the primary studies. Results: Quality of life was defined based on happiness, relationships, independence, religion and life expectancy. Heart failure had a major impact on quality of life, but coping methods were highlighted by patients. Quality of life was evaluated based on comparison to others, level of independence and longevity of life. Conclusions: Quality of life is a multidimensional, subjective term and care should be individualised and holistic to reflect this. Heart failure has a negative effect on quality of life, however, with support and guidance from health care professionals to adapt lifestyle and accept changes, a good quality of life can be maintained. This study has highlight some significant gaps in research that require further investigation.